Activities of Charitable Societies and Institutions in Nizhny Novgorod Province in Second Half of XIX — early XX Century - A. V. Tikhovodova (Научный диалог)
The article is devoted to the work of public charitable organizations and institutions in the Nizhny Novgorod province of the post-reform Russian Empire in various areas of the social sphere. The relevance of the study is due to the development of charitable activities in modern Russia, the need to get acquainted with the historical experience. A review of the activities of voluntary societies, both all-Russian, with branches in Nizhny Novgorod, and, in fact, regional, in the field of social security, health care and public education has been carried out. On the basis of the charters and reports of the companies, their goals, objectives, management structure, sources of funds, forms of assistance to those in need are considered. The author shows the possibilities of social self-organization in the conditions of autocracy, the nature and methods of cooperation between civil society and the authorities. The reasons for the development of charity in the Nizhny Novgorod province in the second half of the XIX century, the motives prompting various segments of the population to engage in it are revealed. The universalism of the work of organizations, in other words unification within the framework of one society of different areas of activity are emphasized in the article. The author comes to the conclusion that the second half of the 19th — the beginning of the 20th century was a period of activity of charitable societies and institutions, whose main obstacle in achieving their goals was a lack of funds.